Fulfilling our commitment to the Caribbean Region: a special IICA report on key projects and achievements 2012 - 2013 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2018)
The International Institute of Cooperation in Agriculture (IICA) is preparing to launch a new Medium-term Plan (MTP) and has reported on key achievements in the Caribbean Region in the 2010-2014 MTP and the Strategic Plan. The report summarizes results achieved in 2012-2013, including projects and initiatives implemented by IICA offices across the 14 Caribbean Member States. The report highlights the initiation of two EU-funded projects: the Agriculture Policy Programme (APP) and an SPS capacity building project. Additionally, two IICA-funded projects on roots and tubers and small ruminants in the Caribbean are also reported on.